Perancangan Sistem Penyedia File Sharing dengan Enkripsi URL menggunakan Algoritma Rijndael - Bhaskara, I Made Adi; Wiharta, Dewa Made; Saputra, Oka (Majalah Ilmiah Teknologi Elektro, 2020)
Information in the digital era is growing very fast, seen from the rapid exchange of information. Information in the form of data or text is widely distributed and can be spread easily and quickly through the website. Generally a website uses website-based programming with the GET method where the GET method has a weakness of system data that can be seen in the access directory. This causes the data in the directory can be taken by unauthorized persons. Based on these problems the file sharing system provider was designed with URL encryption using the rijndael algorithm. The system provides services for sharing data and downloading data securely. Between the provider and recipient of the data each has an application that is an application to upload and an application to download and the admin is tasked with regulating the number of users of the application user. Existing data in the URL shared by the user upload application that has been in the form of an encrypted ciphertext with the shared rijndael algorithm can only be downloaded by the download application user. Each application has an authentication process where only registered users can access the application according to their respective roles. Research that has been done to get the results of encryption conducted on the upload application changes the URL into a ciphertext that can only be downloaded using a download application so that weaknesses in the GET method can be overcome.   Keywords : GET method, encrypt, URL, rijndael algorithm, authentication, download, upload ciphertext